2023
DOI: 10.21511/ee.14(1).2023.06
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of Islamic green financing: A systematic review of green sukuk

Azhar Alam,
Ririn Tri Ratnasari,
Isnani Latifathul Jannah
et al.

Abstract: The threat of the global climate crisis demands improvement and adjustment from various sides, including the financial sector. Islamic finance responds to environmental responsibility by presenting environmentally friendly financing products in green sukuk. This study aims to show the development trend of the number of publications in green sukuk and systematize the results of studies that explain the development and evaluation of the emergence of green sukuk investments. This study analyzed 15 publications on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Several studies in the cited literature have analyzed energy storage for re-electrification or operation within the electrical grid. However, none of these studies provided a tool capable of optimizing the performance of energy storage systems used in both applications while considering electricity market prices and investment opportunities for future investors [32,33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies in the cited literature have analyzed energy storage for re-electrification or operation within the electrical grid. However, none of these studies provided a tool capable of optimizing the performance of energy storage systems used in both applications while considering electricity market prices and investment opportunities for future investors [32,33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This model is based on the implementation of closed cycles in the processes of production, circulation, and consumption, which in the long run leads to a reduction in the negative impact on the environment [15,16]. In [17,18], authors reviewed publications on the subject of green finance and investments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this paper specifically focuses on GS, extensively exploring its various aspects, thereby contributing to the existing literature on financial instruments aimed at combatting climate change; it reviews 62 articles published until June 2023, providing a more comprehensive and up-to-date understanding compared to the 22 studies reviewed by Delle Foglie and Keshminder (2022). Recently, Alam et al. (2023) reviewed only 15 publications from Scopus database, while this study searched six databases and reviewed 62 articles; it identified 11 themes, which surpasses the four GS themes identified by Alam et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Alam et al. (2023) reviewed only 15 publications from Scopus database, while this study searched six databases and reviewed 62 articles; it identified 11 themes, which surpasses the four GS themes identified by Alam et al. (2023).…”
Section: Introductionmentioning
confidence: 99%